Role of vitamin D and E in modulating glucose uptake and insulin sensitivity in insulin-resistant neuronal cells - Zaulkffali, Amirah Salwani (2017)
Alzheimer Disease (AD) has been recognized as a metabolic disease with considerable progressive derangements in brain glucose utilization and responsiveness to insulin. Altered expression of multiple players of insulin signal transduction cascade has led to the qualification of AD as a brain-specific form of diabetes. The aims of this study were to develop an insulin-resistant cell culture model in SK-N-SH neuronal cell line by prolonged exposure to insulin in serum-free medium and to determine the effect of vitamin D and E on insulin signaling. Insulin resistant model is developed via prolonged exposure with 100nM, 150nM, 200nM and 250nM of insulin in serum-free medium. The mRNA expression of insulin signaling markers that involved in glucose transport and Alzheimer’s markers were measured to validate the development of cellular insulin resistance using real-time PCR while AKT phosphorylation was evaluated using ELISA. Insulin treatment significantly reduced the IR, PI3K, GLUT4 and GLUT 3 markers while reduction in AKT phosphorylation and activation of GSK3β were impaired. Further validation on the cellular insulin resistance via glucose uptake assay demonstrated a 15% reduction of insulin resistant upon treatment with 250nM insulin. Determination of vitamin D (10ng/mL and 20ng/mL) and E (200ng/mL) or with both vitamins that involved in alteration of insulin signaling markers and glucose uptake in insulin resistance model were done by measuring the similar markers again. Improvement in insulin signaling pathway was observed upon treatment with vitamin D alone with significant increase in the level of IR, PI3K, GLUT4, GLUT3, glucose uptake as well as AKT phosphorylation while GSK3β and TAU decreased significantly. Meanwhile treatment with vitamin E and combination of both vitamins showed no significant changes in all insulin signaling pathway and Alzheimer’s markers. Contrarily, significant increase in glucose uptake was recorded. Further analysis on the oxidative stress showed vitamin D and E displayed a positive effect in reducing the ROS level. The potential of vitamin E in reducing oxidative stress is postulated to improve signaling pathway leading to improvement of glucose uptake. In conclusion, overall findings indicate that insulin resistance can be developed in SK-N-SH neuronal cell line. Vitamin D and E may demonstrate as an agent that slows the progression of Alzheimer disease caused by insulin resistance in the brain.